BIRTH WEIGHTS OF CROSSBRED CAl!.VES BORN THROUGH ARTIFICIAL INSEMINATION AND EMBRYO TRANSFER - PATEL, D V; KASIRAJ, R; SINGH, S P; NIKHATE, R V; PANCHAL, A G (The Indian Journal of Animal Reproduction, 2023)
The goal of this study was to know whether there is any difference in birth weight (BW) of calves born throughartificial insemination (Al) or Embryo Transfer (ET). The data was collected at SabarmatiAshram Gaushala (SAG)from November, 1997 to June, 2004 taking into consideration the birth of 400 Holstein Friesian x Sahiwal (HF x S)crossbred calves, to eliminate the difference due to breed of dam I sire. All animals were managed under uniformstandard feeding practices. Data was analysed with respect to ET/Al technique, year (1998 to 2004) and season.The Mean values of BW of ET born males and females and Al born males and females were 27. 70±0.60, 25.16±0.53,29.98±0.53 and 26.7 4±0.44 Kg, respectively, with significant differences (P
Keywords: Calves; Birth weight; Artificial insemination; Embryo transfer